ACCIDENT POTENTIAL ESTIMATION SYSTEM BY CALCULATING VEHICLESPEED USING DEEP LEARNING YOLO METHOD (You Only Look Once) - Irman Maulana; sanyata purwidayanta sanyata (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
Traffic accidents are incidents that often lead to serious consequences, such as fatalities or property damage. A key factor influencing these accidents is vehicle speed. Despite some reductions, the death toll from traffic accidents remains high. Vehicle speed, in particular, has been identified as a primary factor exacerbating the risk and severity of accidents. Therefore, controlling vehicle speed is crucial for reducing accident rates.A vehicle speed detection system utilizing deep learning technology, such as the You Only Look Once (YOLO) model, provides an effective solution for analyzing and monitoring vehicle speed in real-time. This technology enables rapid and accurate vehicle detection, along with efficient speed data processing. By leveraging cameras to record video, the system offers essential information for law enforcement and accident prevention. The real-world implementation of this system will enhance traffic safety by delivering relevant and accurate information to authorities. The use of YOLO technology in this system allows for more effective vehicle speed monitoring and prompt decision-making to prevent accidents. Consequently, this system contributes to reducing accident risks and improving road safety.